Are refugees special? - KUKATHAS, Chandran (Institutional Knowledge at Singapore Management University, 2016)
Advocates of restricted immigration usually make an exception for refugees who are described as having special claims to admission on humanitarian grounds. This chapter raises doubts about the plausibility of the distinction between refugees and economic or other non-humanitarian migrants. It argues that the distinction is difficult to draw conceptually and that the institutions designed to serve the interests of refugees in fact aim to limit their capacity to move despite claims that they are intended to serve refugee interests. The chapter also argues that if we want to serve the interests of those who have claims on our help and hospitality we need to devise very different institutional arrangements.